A critical analysis of the legal and institutional frameworks for the realisation of the rights of persons with disabilities in Zimbabwe - Mutangi, Tarisai (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.